A tiered approach to cumulative risk assessment for reproductive and developmental toxicity of food contaminants for the austrian population using the modified Reference Point Index (mRPI). (January 2021) - Vejdovszky, Katharina; Mihats, Daniela; Griesbacher, Antonia; Wolf, Josef; Steinwider, Johann; Lueckl, Johannes; Jank, Bernhard; Kopacka, Ian; Rauscher-Gabernig, Elke
Abstract: Through our daily diet, we are exposed to a variety of food contaminants. Yet, assessing the cumulative health risk of chemical mixtures remains a challenge. Using a recently developed method, the modified Reference Point Index (mRPI), the cumulative risks posed by contaminant mixtures were assessed for their effects on reproduction and development. Since these effects can be quite diverse, a tiered approach was adopted to elucidate the risks at a more detailed level based on specific toxicological endpoints. An additional analysis was performed using the modified Maximum Cumulative Ratio (mMCR), which provides the determination of risk-dominating substances in the mixture. Our method represents a novel useful tool to screen and prioritise contaminant mixtures regarding their potential health risks. We found, that in the majority of the calculated scenarios a single substance dominates the cumulative risks. Lead was found to be the primary factor for adverse effects on reproduction and neuronal development of children. Perchlorate was identified as the most prominent risk factor for child development in generalCumulative risks of trichothecenes were dominated by deoxynivalenol. Concerning the impact on pre- and neonatal development, the co-exposure of several substances resulted in increased risks, with none of the considered contaminants dominating substantially. Highlights: The mRPI facilitates prioritisation of contaminant mixtures according to health risks. CAGs of contaminants are proposed for development and reproduction. First assessment for food contaminant mixtures regarding cumulative risks to development and reproduction. Lead, Perchlorate and Deoxynivalenol dominate specific cumulative risks. Cumulative risks for pre- and neonatal development emerge from mixture exposure.